2015
DOI: 10.1016/j.matlet.2015.01.149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion concentration on mechanosynthesis of carbonated chlorapatite nanopowders

Abstract: a b s t r a c tCarbonated chlorapatite nanopowders (n-CCAp) with different degrees of substitution were successfully synthesized by the one-step mechanochemical process. Results demonstrated that the formation of n-CCAp was influenced strongly by the carbonate content (x). From X-ray analysis, crystallite size, crystallinity degree, and unit cell volume of n-CCAp decreased significantly as carbonate content (x) increased from 0 to 2. Conversely, the lattice strain and the volume fraction of grain boundaries gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The spectral peaks at 3569, 3250, 3200, 2420, 1705, 1470, 1405 and 1104 cm À1 of the ground product (mainly peaks due to DCPD) decrease with increasing grinding time. In contrast, the peaks at 600 and 1000 cm À1 due to the carbonated apatite and 3 due to the phosphate ion significantly increase 35 . The results indicated that this phenomenon is a transition to a HAp-like solid.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The spectral peaks at 3569, 3250, 3200, 2420, 1705, 1470, 1405 and 1104 cm À1 of the ground product (mainly peaks due to DCPD) decrease with increasing grinding time. In contrast, the peaks at 600 and 1000 cm À1 due to the carbonated apatite and 3 due to the phosphate ion significantly increase 35 . The results indicated that this phenomenon is a transition to a HAp-like solid.…”
Section: Resultsmentioning
confidence: 84%
“…SEM results (Figure 4a) clearly indicated that the product had a clusterlike structure that was composed of several small particles with 5 lm or less in diameter. Fahami et al 35 reported an effect of ion concentration on mechanosynthesis of carbonated chlorapatite nanopowders, and concluded that the formation of a ductilebrittle system induced polygonal shape nanocrystals. In the present system, during milling, three brittle components (ZnO, CaO and CaHPO 4 ) were transformed into amorphous forms with a deformed and unstable nature.…”
Section: Formation Of the Zn-doped Caps By Wet Mechanochemical Synthesismentioning
confidence: 99%
“…Carbonated chlorapatite nanopowders can be synthesized by the mechanochemical process under argon atmosphere using the mixture of calcite (CaCO 3 ), phosphorus pentoxide (P 2 O 5 ) and calcium chloride (CaCl 2 ) as raw materials [181], [182]:…”
Section: Carbonate-chlorapatitesmentioning
confidence: 99%
“…Finally, a balance between fracturing brittle particles by trapping and ductile constituents by work hardening caused the formation of fine powders [29].…”
Section: Morphological Characterization (Tem Analysis)mentioning
confidence: 99%